2015
DOI: 10.4028/www.scientific.net/amm.815.148
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Fire Retardant Effect in Natural Fiber Composite Panels with Magnesium Hydroxide and Zinc Borate as Additives

Abstract: The objective of this study is to investigate the fire retardancy effect of coconut coir, rice husk and sawdust panels which are incorporated with magnesium hydroxide (Mg (OH)2) and zinc borate (2ZnO∙3B2O3∙3.5H2O) as additives. The natural fiber and additives are mixed and cured for one week, with polyester resin and hardening catalyst as binders. Fire retardancy of these panels are tested according to American Society for Testing and Materials (ASTM) Horizontal (D 365) and Vertical Burning (D 3801) tests. Pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…Even in low quantities, these chemicals are highly toxic. [ 28 ] Though, in contour with the global measure on the road to a greener environment, so it is strongly preferable to use halogen‐free FR rather than halogenated FR. [ 29 ] Different halogen‐free flame retardants exist like nitrogen‐based, intumescent types, metal hydrates, and phosphorus‐based.…”
Section: Introductionmentioning
confidence: 99%
“…Even in low quantities, these chemicals are highly toxic. [ 28 ] Though, in contour with the global measure on the road to a greener environment, so it is strongly preferable to use halogen‐free FR rather than halogenated FR. [ 29 ] Different halogen‐free flame retardants exist like nitrogen‐based, intumescent types, metal hydrates, and phosphorus‐based.…”
Section: Introductionmentioning
confidence: 99%
“…The use of FRs for NFRP composites may inhibit or even suppress the combustion processes, for example during heating, decomposition, ignition, and flame spread [21]. Studies have shown that it is possible to enhance the fire resistance of NFRP composites by the incorporation of fire-retardant additives such as halogen, nitrogen and phosphorus-based compounds [22,23,24].…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the polymer, additives, and fire conditions, gases such as hydrogen chloride (HCl), hydrogen fluoride (HF), hydrogen cyanide (HCN), and carbon monoxide (CO) may be produced in varying quantities from a burning composite. These compounds are considered toxic even at relatively low concentrations [23,24]. Phosphorus-based fire retardants are considered safer alternatives.…”
Section: Introductionmentioning
confidence: 99%